The Rif Chain (Northern Morocco) in the Late Tortonian‐Early Messinian Tectonics of the Western Mediterranean Orogenic Belt: Evidence From the Tanger‐Al Manzla Wedge‐Top Basin. Issue 9 (22nd September 2020) - Abbassi, A.; Cipollari, P.; Zaghloul, M. N.; Cosentino, D.
Abstract: During the Neogene, the Western Mediterranean subduction‐related orogen developed under differing modes and senses of subduction, resulting in the formation of the Apennines, Maghrebides, Rif, and Betics. In this work, we present the Neogene kinematic evolution of the Rif, based on literature data and new results from structural‐stratigraphic analyses and biostratigraphic investigations carried out in the External Zone of the Rif. We analyzed three stratigraphic sections: Dar Zhirou, Saf Lahmame, and Seguedla. The results of these analyses allow us to reconstruct a wide Tortonian‐Messinian wedge‐top basin in the Tanger‐Al Manzla area, when the leading edge of the Rif was at the frontal thrust of the Prerif. The presence of this wedge‐top basin points to a Tortonian‐Messinian compressional deformation that affected a wide area of the Rif, including the Prerif, Mesorif, and Intrarif. The late Miocene compressional deformation that affected the Mesorif and Intrarif occurred as out‐of‐sequence thrusting, due to renewed compressional tectonics in the internal zone of the chain triggered by the collision of the Rif accretionary wedge with the North African Margin. In the Neogene evolution of the Western Mediterranean subduction‐related orogen, the late Miocene was a major pulse in the interplay between African and European plates, as evidenced by the increase in migration rates of some segments of the circum‐Mediterranean fold‐and‐thrust belt, the out‐of‐sequence thrusting in the Rif, as well as the occurrence of late Miocene imbricate thrust structures in oceanic fracture zones of the African Plate (Central Atlantic Ocean). Key Points: The analyses performed allow us to reconstruct a wide Tortonian‐Messinian wedge‐top basin in the Tanger‐Al Manzla area The Tanger‐Al Manzla wedge‐top basin demonstrates that the Intrarif was affected by compressional tectonics during the late Miocene The collision of the late Miocene Rifian accretionary wedge with the Meseta induced out‐of‐sequence thrusting in the Mesorif and Intrarif